When neighbors play a role: A systems-level analysis of protein interactions conditioning cancer driver mutation effects - João A. I. Miranda; Márcia F. S. Vital; Margarida Carrolo; António Quintela; Francisco R. Pinto (Proceedings of the National Academy of Sciences, 2025)
Cancer is driven by the accumulation of somatic mutations, including driver mutations that confer a selective advantage to cancer cells. Driver proteins operate within complex interaction networks, and their activity is conditioned by neighbor proteins. Understanding the interplay between driver mutations and the expression of their neighbor proteins can provide insights into cancer biology and potential therapeutic targets. We assessed associations between expression of neighbor proteins and driver mutation status, comparing both between and within cancer types. We further evaluated if neighbors were enriched in significant associations with multiple drivers and characterized the impact of neighbor expression on overall survival for all cancer types. We found a significant correlation between the number of driver associations (DA) a neighbor gene has and the number of sign-coherent survival associations, particularly for neighbors enriched in positive associations, where high neighbor expression correlated with increased driver mutations and poorer survival. We identified 119 neighbors enriched in positive DA with at least two unfavorable survival associations and 25 neighbors enriched in negative DA with at least two favorable survival associations. Our study systematically identified neighbors associated with driver mutation status. Complementary evidence from survival analysis and the literature suggests that neighbors enriched in DA can be further explored as drug target candidates.